Islamic Songs for Children (Immerse Morals or Religious Understanding toward Children) - Dewi Suriyani Djamdjuri (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2015)
Learning a language for children will be much more effective when it is done while doing interesting and fun activities. One of the activities to be used is the application of English songs. This present research describes discourse analysis on the content of Islamic songs and their beneficial effect in moral teaching and understanding of the children. It is expected that through the use of Islamic songs, children can both build their English skill and grow with religious understanding.